2002
DOI: 10.1111/j.1939-1676.2002.tb01610.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Enalapril for Prevention of Congestive Heart Failure in Dogs with Myxomatous Valve Disease and Asymptomatic Mitral Regurgitation

Abstract: We evaluated the long-term effect of early angiotensin-converting enzyme (ACE) inhibition (enalapril maleate) as monotherapy to postpone or prevent congestive heart failure (CHF) in asymptomatic dogs with mitral regurgitation (MR) attributable to myxomatous valvular disease (MVD) in a prospective, randomized, double-blinded, placebo-controlled multicenter trial involving 14 centers in Scandinavia. Two hundred twenty-nine Cavalier King Charles (CKC) Spaniels with MR attributable to MVD but no signs of CHF were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
61
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 142 publications
(65 citation statements)
references
References 26 publications
3
61
0
Order By: Relevance
“…Although in the latter study MR was not assessed using a Doppler method, we can hypothesize that all the recruited dogs had severe (although compensated) MR, because left atrial enlargement on M‐mode or 2D echocardiography was one of the inclusion criteria 9 . Interestingly, in the SVEP trial, although MR severity was not assessed (because dogs were evaluated at entry only by physical examination, ECG, and thoracic radiographs), CKC with an initial heart murmur of moderate intensity showed a markedly shorter time to CHF than in dogs with low‐intensity murmurs 10 . This may also be related to MR severity because a significant correlation has been demonstrated in the CKC breed between heart murmur grade and MR severity as assessed by ARJ/LAA 36 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although in the latter study MR was not assessed using a Doppler method, we can hypothesize that all the recruited dogs had severe (although compensated) MR, because left atrial enlargement on M‐mode or 2D echocardiography was one of the inclusion criteria 9 . Interestingly, in the SVEP trial, although MR severity was not assessed (because dogs were evaluated at entry only by physical examination, ECG, and thoracic radiographs), CKC with an initial heart murmur of moderate intensity showed a markedly shorter time to CHF than in dogs with low‐intensity murmurs 10 . This may also be related to MR severity because a significant correlation has been demonstrated in the CKC breed between heart murmur grade and MR severity as assessed by ARJ/LAA 36 .…”
Section: Discussionmentioning
confidence: 99%
“…However, unlike tolerability, conflicting results have been obtained regarding ACEIs efficacy on asymptomatic canine MVD. In the SVEP trial, 10 the number of CKC developing CHF was similar in the treatment and placebo group, and treatment with enalapril did not delay the onset of CHF regardless of whether or not cardiomegaly was present at initiation of the study. Conversely, the follow‐up of dogs recruited from the VETPROOF study (Veterinary Enalapril Trial to Prove Reduction in Onset Of heart Failure) demonstrated that chronic enalapril therapy was effective in delaying the onset of CHF and had a benefit on the combined endpoint of CHF–all‐cause death 9 …”
mentioning
confidence: 91%
See 3 more Smart Citations